Hubungan Kualitas Susu Dengan Adopsi Inovasi Pemanfaatan Teknologi Biogas di Daerah Jalur Susu Malang sampai Pasuruan - Djoko Winarso; Herawati Herawati (Universitas Muhammadiyah Purworejo, 2016)
This study aims to determine differences in the quality of milk at the level of livestock farmers between before and after the adoption of innovation in the use of biogas technology. The research design to analyze the quality of the milk used a completely randomized design (CRD) and the results were analyzed using the least significant difference (LSD) test. To determine the characteristics of livestock farmers and the distribution of biogas innovation adoption categories, a quantitative descriptive method was used. The results showed that the profile of internal characteristics of livestock farmers was quite potential, the profile of potential external characteristics and the distribution of biogas utilization innovation adoption categories, namely the Innovators 10.25%, 38.46% Early Adopters, 34.61% Early Majority and 16 Late Majorities 66%. The conclusion of this study is that the quality of milk that is checked before and after the adoption of biogas innovation shows a significant difference.